Performa Komponen Hasil dan Karakter Agronomi berbagai Genotipe Galur Cabai Rawit - Winda Saskia Sijabat; Muhamad Syukur; Arya Widura Ritonga; Muhammad Ridha Alfarabi Istiqlal; Abdul Hakim; Arya Yuda Pangestu; Okti Syah Isyani Permatasari; Siti Marwiyah; Sulassih Sulassih; Zulfikar Damaralam Sahid (Agrotechnology Research Journal, 2023)
Cayenne pepper is one of the important horticultural commodities and has high economic value for Indonesian people. The demand for cayenne pepper in Indonesia was relatively high, especially for household consumption. Therefore, superior varieties were needed to meet the needs of cayenne pepper in Indonesia. One way to guarantee the superiority of varieties and the validity of variety descriptions was to conduct yield testing. Our research aims to evaluate the performance and yield of seven genotypes of cayenne pepper. This research was carried out from March 2023 to September 2023 at Leuwikopo Experimental Garden, IPB University. It consisted of one factor: ten genotypes (seven genotypes and three control varieties). Experimental design in our research using randomized complete block design with three replications. The results showed that there were differences in performance and yield between cayenne pepper genotypes. The flowering ages of all genotypes ranged from 41.33 - 45.67 DAP with the harvest ages ranging from 83.33 - 92.67 DAP. The percentage of plants observed at the end of harvest ranged from 37.50 - 70.83% with the Rawita F1 variety showing the lowest percentage (37.50%). F1.372340 genotype was the highest productivity genotype, reaching 4.80 t.ha-1. The productivity of F1.372340 was higher than control varieties, which ranged from 1.48 to 2.72 t.ha-1. Line’s genotype had a shelf life ranging from 9.30 - 15.00 DAH which was the same or better than the control varieties which ranged from 9.67-12.33 DAH.